2021
DOI: 10.1080/21655979.2021.2009967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature-sensitive nanogel combined with angioplasty on sICAM-1 and VE-cadherin in lower extremity arterial occlusion rabbits

Abstract: The study was to explore the effect of subintimal angioplasty (SIA) on the levels of soluble intercellular adhesion molecule-1 (sICAM-1) and vascular endothelial cadherin (VE-cadherin) in the rabbit model of lower extremity arterial occlusion. Specifically, the poly(N-isopropylacrylamide-co-butyl methacrylate) (PIB) temperature-sensitive nanogel was prepared, and the cytotoxicity of direct and indirect contact with PIB temperature-sensitive gel was analyzed then. Subsequently, the PIB temperature-sensitive gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Atherosclerotic occlusion is involved in endothelial cell dysfunction and migration, thrombus formation, and vascular remodeling with resultant local inflammation and cytokine release (Qi et al 2021). The high-fat diet-induced LEASO rats showed high levels of TC, IL-1, and TNF-α, Excessive apoptosis of endothelial cells is preliminary in atherosclerosis, and inhibiting apoptosis may prevent and treat atherosclerosis (Duan et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic occlusion is involved in endothelial cell dysfunction and migration, thrombus formation, and vascular remodeling with resultant local inflammation and cytokine release (Qi et al 2021). The high-fat diet-induced LEASO rats showed high levels of TC, IL-1, and TNF-α, Excessive apoptosis of endothelial cells is preliminary in atherosclerosis, and inhibiting apoptosis may prevent and treat atherosclerosis (Duan et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…50 Previous studies have fully confirmed the strong biocompatibility of pNIPAm and QAS-pNIPAm. 51,52 γ-PGA, a common food and skin care additive, also exhibits excellent biocompatibility and degradability. 53,54 Another possible source for cytotoxicity of the nanogels is the release of CaP; however, in previous studies, Ca-induced cytotoxicity was specifically selective in tumour cells but biologically safe in normal cells.…”
Section: Biocompatibilitymentioning
confidence: 99%